5(x+16)=5^2.4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3/4.8/9.15/16......9999/10000
= 3.8.15.....9999/4.9.16......10000
=101/50
a; \(\dfrac{5}{6}\) + \(\dfrac{5}{12}\) + \(\dfrac{5}{20}\) + ... + \(\dfrac{5}{132}\)
= 5.(\(\dfrac{1}{6}\) + \(\dfrac{1}{12}\) + \(\dfrac{1}{20}\) + ..+ \(\dfrac{1}{132}\))
= 5.(\(\dfrac{1}{2.3}\) + \(\dfrac{1}{3.4}\) + ... + \(\dfrac{1}{11.12}\))
= 5.(\(\dfrac{1}{2}\) - \(\dfrac{1}{3}\) + \(\dfrac{1}{3}\) - \(\dfrac{1}{4}\) + ...+ \(\dfrac{1}{11}\) - \(\dfrac{1}{12}\))
= 5.(\(\dfrac{1}{2}\) - \(\dfrac{1}{12}\))
= 5.(\(\dfrac{6}{12}\) - \(\dfrac{1}{12}\))
= 5.\(\dfrac{5}{12}\)
= \(\dfrac{25}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=1,4 x\(\dfrac{15}{49}-\) \(\left(\dfrac{4}{5}+\dfrac{2}{3}\right)\) : 2\(\dfrac{1}{5}\)
= \(\dfrac{3}{7}\) - \(\dfrac{22}{15}\) : \(\dfrac{11}{5}\)
= \(\dfrac{3}{7}\) - \(\dfrac{2}{3}\)
= \(-\dfrac{5}{21}\)
( 2\(\dfrac{1}{5}\) + \(\dfrac{3}{5}\) \(\times\) \(x\)) = \(\dfrac{3}{4}\)
\(\dfrac{11}{5}\) + \(\dfrac{3}{5}\)\(x\) = \(\dfrac{3}{4}\)
\(\dfrac{3}{5}\)\(x\) = \(\dfrac{3}{4}\) - \(\dfrac{11}{5}\)
\(\dfrac{3}{5}\)\(x\) = - \(\dfrac{29}{20}\)
\(x\) = -\(\dfrac{29}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2,4*x-36):(1+5/7)=-14
(2,4*x-36): 12/7 =-14
2,4*x-36= -14*12/7
2,4*x-36= -4
2,4*x= -4+36
2,4*x= 32
x=32:2,4
x= 40/3 vậy x= 40/3
Tick nha
![](https://rs.olm.vn/images/avt/0.png?1311)
6x+2.4=5^3:5^2+9
6x+8=5+9
6x+8=14
6x=14-8
6x=6
x=6:6
x=1
(5^3 là 5 mũ 3,5^2 là 5 mũ 2)
![](https://rs.olm.vn/images/avt/0.png?1311)
6x+2.4=5\(^3\):5\(^2\)+9
6x+8=5+9
6x+8=14
6x=14-8
6x=6
x=6:6
x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2.4:\left(\frac{-1}{2}-x\right)=\frac{8}{5}\)
\(8:\left(\frac{-1}{2}-x\right)=\frac{8}{5}\)
\(\frac{-1}{2}-x=5\)
\(x=\frac{-55}{10}\)
Vậy \(x=\frac{-55}{10}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(X-140)^3:7^2=4^5-3^2.4^3.
=>(x - 140)3:72 = 45 - 32.43
(x - 140)3 : 49 = 448
(x - 140)3 = 21952 = 282
x - 140 = 28
x = 168
5 (x +16) = 52 . 4
5 ( x + 16) = 100
x + 16 = 100 : 5
x + 16 = 20
x = 20 - 16
x = 4